Pengaruh kinerja keuangan sebelum dan selama adanya pandemi Covid-19 terhadap harga saham pada laporan keuangan klub sepak bola - Wahyuni, Sri; Bhilawa, Loggar (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze financial performance's effect on football clubs' share prices before and during the Covid-19. Financial performance in this study is measured by the profitability, liquidity and solvency ratio. This research will use quantitative research methods with secondary data sources in the form of archives of financial statements of football clubs listed on various stock exchanges and Public shares in 2019/2020 and 2020/2021. The analysis technique used in this study is a multiple linear regression analysis techniques. The results of this study show the results that the profitability ratio measured by Return On Investment, liquidity ratio is measured by Current Ratio and Cash Ratio, and solvency ratio measured by Debt to Assets Ratio and Debt to Equity Ratio have no effect and are not significant to the share price of football clubs both before and during Covid-19.